2000
DOI: 10.1161/01.cir.101.16.1925
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Spares Myocardial Oxygen Consumption Through Attenuation of Contractile Response to β-Adrenergic Stimulation in Patients With Idiopathic Dilated Cardiomyopathy

Abstract: Background-The results of recent studies suggest that NO synthase may increase in the failing myocardium and that NO modulates the myocardial contractile response to ␤-adrenergic stimulation. However, there are few data regarding the physiological role of NO in patients with heart failure. The aim of the present study was to address the role of NO in left ventricular (LV) contractile response to ␤-adrenergic stimulation and corresponding oxygen expenditure in human heart failure. Methods and Results-We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
(33 reference statements)
2
31
1
2
Order By: Relevance
“…This may represent a primary endothelial effect; as in nonischemic cardiomyopathy, preserved endothelial function has been associated with improved clinical outcomes, 27 and exacerbation of endothelial dysfunction may underlie the adverse impact of the Asp 298 variant in this subset. Alternatively, given the modulation of adrenergic signaling by NO, 8,9 the impact of the Asp 298 variant in nonischemic outcomes may reflect a primary influence on cardiomyocyte function. This study demonstrates that for patients with heart failure, genetic variation of NOS3 contributes to the observed heterogeneity of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may represent a primary endothelial effect; as in nonischemic cardiomyopathy, preserved endothelial function has been associated with improved clinical outcomes, 27 and exacerbation of endothelial dysfunction may underlie the adverse impact of the Asp 298 variant in this subset. Alternatively, given the modulation of adrenergic signaling by NO, 8,9 the impact of the Asp 298 variant in nonischemic outcomes may reflect a primary influence on cardiomyocyte function. This study demonstrates that for patients with heart failure, genetic variation of NOS3 contributes to the observed heterogeneity of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6 TNF administration to myocytes induces expression of NOS2, 7 which mediates its cardiodepressant effects. NO diminishes the effect of ␤-agonist stimulation on contractility, 8,9 potentially limiting the impact of sympathetic activation on disease progression. Given the effects on adrenergic response and the peripheral vasculature, an increase in NOS activity and NO production can be postulated to have a cardioprotective effect in heart failure.…”
mentioning
confidence: 99%
“…Nonselective NOS inhibition enhances the inotropic response to ␤-adrenergic stimulation in patients and dogs with CHF. 27,28 If the increased MV O 2 after NOS inhibition were due to an enhanced catecholamine response, however, then the effect would probably have been most prominent during exercise, when catecholamines are further increased, in contrast to the observed parallel upward shift in the relationship between MV O 2 rate-pressure product. Finally, it is likely that the increase of MV O 2 resulted in part from the increased arterial and LV systolic pressure that occurred in response to NOS inhibition in animals with CHF.…”
Section: No In Chfmentioning
confidence: 99%
“…3,4 Previous studies have shown that inhibition of cardiac NO synthase (NOS) augments the positive inotropic response to -adrenergic receptor stimulation in human heart failure, suggesting that increased activity of myocardial NOS and NO attenuates -adrenergic responsiveness. [5][6][7] In patients with severe CHF, the increase in intracellular cyclic AMP and myocardial contractility in response toadrenergic receptor stimulation is reduced, 5 which reflects cardiac desensitization to -receptor agonists, 8 partly modulated by the increased production of NO in the myocardium. 5 Previous studies have shown that forskolin produces beneficial cardiac effects by directly stimulating adenylyl cyclase in the failed human heart, especially in those with a relative insensitivity to -adrenergic receptor stimulation.…”
mentioning
confidence: 99%